Soil Application of Zinc Fertilizer Increases Maize Yield by Enhancing the Kernel Number and Kernel Weight of Inferior Grains - Liu, Dun-Yi; Zhang, Wei; Liu, Yu-Min; Chen, Xin-Ping; Zou, Chun-Qin (Frontiers in Plant Science, 2020)
Improving the development of inferior grain is important for increasing maize yield under high-density conditions. However, the effects of micronutrients, especially zinc (Zn), on the development of inferior grains and the maize yield under field conditions have not been reported. A field experiment with six Zn application rates (0, 2.3, 5.7, 11.4, 22.7, and 34.1 kg/ha) was conducted to investigate the effects and mechanism of soil application of Zn fertilizer on the development of inferior grains. Pollen viability was measured at the tasseling stage. The maize spike was divided into apical (inferior grain), middle, and basal sections for further measurement at harvest. Results showed that soil application of Zn fertilizer increased maize yield by 4.2–16.7% due to increased kernel number and weight in the apical, but not in the middle and basal sections. Zn application also significantly increased pollen viability at the tasseling stage. The critical Zn concentrations in shoots at the tasseling stage for obtaining high pollen viability and high kernel numbers of inferior grains were 31.2 and 35.6 mg/kg, respectively. Zn application also increased the 1000-kernel weight of inferior grain due to high biomass accumulation. Furthermore, the grain Zn concentration of inferior grain with Zn application increased by 24.3–74.9% compared with no Zn application. Thus, soil application of Zn fertilizer succeeded in increasing grain yield of maize by improving pollen viability, kernel number, and kernel weight of inferior grains (apical section); it also contributed to grain Zn biofortification.